Características de los procesos penales (investigación previa al juicio y juicio) en el momento de la pandemia covid-19 - Larysa Bielik; Olena Samoilenko; Hanna Mudretska; Tetiana Voloshanivska; Kateryna Titunina (Universidad Hemisferios, 2020)
The work is devoted to the main problems and features that have emerged in the field of criminal justice (pre-trial investigation and trial) in a pandemic. The relevance of this article is that criminal justice, like other areas of human activity, has been affected after the spread of Covid-19 and its recognition as a pandemic. The introduction of quarantine was accompanied by some problematic issues, including uncertainty in the work of the judiciary and law enforcement agencies, lack of a unified approach to court schedules, and the conduct of certain investigative actions. Thus, it is necessary to analyze the peculiarities of criminal proceedings in a pandemic. An explorative and collative methodology (that considers the comparative law) was used. The proposals have been made to address the problems that arise during the pre-trial investigation and criminal proceedings in a pandemic, in particular: the need to allow videoconferencing in criminal proceedings out of court; a list of programs for video communication have been defined; to provide adequate funding for technical re-equipment; to suspend the terms of criminal proceedings, and; to prevent in the future the situation of cancellation of previously adopted decisions on the strengthening of criminal liability for intentional infection.